A quantitative tumor‐wide analysis of morphological heterogeneity of colorectal adenocarcinoma - Mihnea P Dragomir; Vlad Popovici; Simon Schallenberg; Martina Čarnogurská; David Horst; Rudolf Nenutil; Fred Bosman; Eva Budinská (The Journal of Pathology: Clinical Research, 2025)
Abstract The intertumoral and intratumoral heterogeneity of colorectal adenocarcinoma (CRC) at the morphologic level is poorly understood. Previously, we identified morphological patterns associated with CRC molecular subtypes and their distinct molecular motifs. Here we aimed to evaluate the heterogeneity of these patterns across CRC. Three pathologists evaluated dominant, secondary, and tertiary morphology on four sections from four different FFPE blocks per tumor in a pilot set of 22 CRCs. An AI‐based image analysis tool was trained on these tumors to evaluate the morphologic heterogeneity on an extended set of 161 stage I–IV primary CRCs (n = 644 H&E sections). We found that most tumors had two or three different dominant morphotypes and the complex tubular (CT) morphotype was the most common. The CT morphotype showed no combinatorial preferences. Desmoplastic (DE) morphotype was rarely dominant and rarely combined with other dominant morphotypes. Mucinous (MU) morphotype was mostly combined with solid/trabecular (TB) and papillary (PP) morphotypes. Most tumors showed medium or high heterogeneity, but no associations were found between heterogeneity and clinical parameters. A higher proportion of DE morphotype was associated with higher T‐stage, N‐stage, distant metastases, AJCC stage, and shorter overall survival (OS) and relapse‐free survival (RFS). A higher proportion of MU morphotype was associated with higher grade, right side, and microsatellite instability (MSI). PP morphotype was associated with earlier T‐ and N‐stage, absence of metastases, and improved OS and RFS. CT was linked to left side, lower grade, and better survival in stage I–III patients. MSI tumors showed higher proportions of MU and TB, and lower CT and PP morphotypes. These findings suggest that morphological shifts accompany tumor progression and highlight the need for extensive sampling and AI‐based analysis. In conclusion, we observed unexpectedly high intratumoral morphological heterogeneity of CRC and found that it is not heterogeneity per se, but the proportions of morphologies that are associated with clinical outcomes.